2015
DOI: 10.4103/0974-8490.147197
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral toxicity studies of Swietenia macrophylla seeds in Sprague Dawley rats

Abstract: Background:Swietenia macrophylla King. (Meliaceae) seeds (SMS); commonly known as sky fruit and locally known in Malaysia as Tunjuk Langit; have been used in traditional Malay medicine for the treatment of diabetes and hypertension. The people eat only a tiny amount of raw seed, weighing not more than 5 mg.Aim:To evaluate the safety of Swietenia macrophylla seeds (SMS) at a single-dose oral administration of 2 g/kg body weight (bw) in sprague dawley (SD) rats.Materials and Methods:Eight-week old male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…The same way Peristrophe bivalvis extracts with antivenom potential to Naja kaouthia and Trimeresurus albolabris, did not show toxic signs in rats (27) The toxicity of the seed extract of various species of Swietenia were previously described, in a recent study of acute oral toxicity of the seed extract from Swietenia mahagoni in a murine model, lesions suggestive of organ toxicity at doses of 25, 200 2000, 5000 mg/kg were not observed (28). In another study which the acute oral toxicity of seed extract from Swietenia macrophylla in rats at doses of 2000 mg/kg was evaluated, the results showed that seeds did not produce significant differences in weight, food and water intake, biochemical and hematological parameters, or macroscopic and histopathological changes in the organs of the treated animals compared with controls (6).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The same way Peristrophe bivalvis extracts with antivenom potential to Naja kaouthia and Trimeresurus albolabris, did not show toxic signs in rats (27) The toxicity of the seed extract of various species of Swietenia were previously described, in a recent study of acute oral toxicity of the seed extract from Swietenia mahagoni in a murine model, lesions suggestive of organ toxicity at doses of 25, 200 2000, 5000 mg/kg were not observed (28). In another study which the acute oral toxicity of seed extract from Swietenia macrophylla in rats at doses of 2000 mg/kg was evaluated, the results showed that seeds did not produce significant differences in weight, food and water intake, biochemical and hematological parameters, or macroscopic and histopathological changes in the organs of the treated animals compared with controls (6).…”
Section: Discussionmentioning
confidence: 90%
“…Its seeds have many uses, such as in the traditional treatment of hypertension, diabetes and to relieve pain in Malaysia, to treat leishmaniosis and to induce abortion in Bolivia, as well as for the treatment of diabetes, hypertension and malaria in Indonesia. In addition, its bark is used as an astringent for wounds and occasionally for sun tanning (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are used to treat diabetes and hypertension. In 2015, Balijepalli [ 22 ] evaluated the safety of SMS in Sprague-Dawley (SD) rats. Their conclusion was that the rat dose of 2 g/kg bw, which is equivalent to the human dose of 325 mg/kg bw and well below the common amount that is consumed by people, did not exhibits any signs of toxicity in rats.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Histological changes in the main organs (the liver, kidney, spleen, heart, intestine, lung and brain) were graded on a scale of 0–9 based on the degree of architecture degeneration, inflammation and necrosis [ 16 ].…”
Section: Methodsmentioning
confidence: 99%